The use of multi-energy photon emitters in 3D SPECT reconstruction. (January 2019) - Szlávecz, Á.; Hesz, G.; Benyó, B.
Highlights: SPECT reconstruction strategies are suggested for multi-energy isotopes. The reconstruction strategies are compared by mathematical phantom studies. Multi-energy data acquisition can be used to improve image quality. Differences in reconstruction time are experienced with similar image quality. Abstract: Several regularly used tracers in SPECT imaging are multi-energy photon emitters, which emit gamma photons at different energy levels. This study introduces different alternative reconstruction methods with attenuation correction and detector response compensation that enable the use of projection images generated by multi-energy photon emitters. The suggested alternative reconstruction scenarios are compared by simulation studies. The applied tracer was Gallium-67 with three photopeaks. Non-homogeneous attenuation medium and distance dependent spatial resolution (DDSR) of the parallel imaging device was modelled in the study. All the reconstruction algorithms compensated the energy dependent nature of the above two phenomena, in a different way. These suggested reconstruction scenarios differ in data acquisition strategy (i.e. summing up all energy windows into one projection image series or storing them separately) and in the energy dependent calculation of the forward projection during reconstruction. The presented reconstruction strategies have been compared using different mathematical phantoms such as a ring phantom in inhomogeneous attenuating medium, the Derenzo phantom, and the NCAT phantom.